PPO.03 Effects of maternal nutrition and ruminal-protected arginine supplementation on offspring growth. (9th June 2014) - Peine, JL; Jia, GQ; Van Emon, ML; Neville, TL; Kirsch, JD; Hammer, CJ; O'Rourke, ST; Reynolds, LP; Caton, JS
Abstract : Our hypothesis was that arginine supplementation would overcome the negative effects of restricted maternal intake during the last two-thirds of gestation on offspring growth. Multiparous, Rambouillet ewes (n = 32) were allocated to 3 treatments in a completely random design at 54 ± 3.9d of gestation. Dietary treatments were 100% of requirements (control, CON), 60% of control (restricted, RES), or RES plus a rumen-protected arginine supplement dosed at 180 mg/kg body weight (BW) once daily (RES-ARG). Ewes were penned individually in a temperature-controlled facility. Lamb birth weight was greater ( P = 0.04) in CON than RES ewes, and tended ( P = 0.10) to be greater in CON vs. RES-ARG. Lambs born to CON ewes had greater ( P ≤ 0.03) BW than lambs from RES ewes at 7, 14, and 33d postpartum. On d19, lambs from CON and RES-ARG ewes both had greater ( P ≤ 0.04) BW than lambs from RES ewes (12.0 and 11.5 vs. 10.3 ± 0.41kg, respectively). Lambs born to CON and RES-ARG ewes had greater ( P ≤ 0.04) weight gain than lambs from RES ewes on d19 (355.0 and 354.0 vs. 306.4 ± 15.77g, respectively). Lambs from CON and RES-ARG ewes also had greater ( P ≤ 0.02) girth circumference than lambs from RES ewes on d19 (55.4 and 54.6 vs. 51.3 ± 0.97cm, respectively). On d54, lambs from RES-ARG ewes had greater ( P = 0.003) body length than lambs from RES ewes (99.8 vs. 93.9 ± 1.28cm, respectively). Results confirm our hypothesis that arginine supplementation during the last two-thirds of gestation can mitigate some negative consequences in offspring associated with restricted maternal nutrition. (Presented previously; WSASAS, June 19–21, 2013).